2017
DOI: 10.3390/ijerph14091041
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles, Glycated Hemoglobin, and Diabetes in People Living at High Altitude in Nepal

Abstract: This study aimed to describe lipid profiles and the distribution of glycated hemoglobin (HbA1c) in a sample of a high altitude population of Nepal and to explore associations between these metabolic risk variables and altitude. A cross-sectional survey of cardiovascular disease and associated risk factors was conducted among 521 people living at four different altitude levels, all above 2800 m, in the Mustang and Humla districts of Nepal. Urban participants (residents at 2800 m and 3620 m) had higher total cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…This is one of few studies, which explores the association of routine lipid parameters with T2DM and prediabetes in Bangladesh. Low HDL-C and high Tg dyslipidemia are more prevalent in our population than in the other South Asian populations [ 8 , 54 ] and have shown stronger association with T2DM and prediabetes. In clinical practice in Bangladesh, T-Chol, Tg, HDL-C, and LDL-C are the parameters available for monitoring lipid abnormalities.…”
Section: Discussionmentioning
confidence: 83%
“…This is one of few studies, which explores the association of routine lipid parameters with T2DM and prediabetes in Bangladesh. Low HDL-C and high Tg dyslipidemia are more prevalent in our population than in the other South Asian populations [ 8 , 54 ] and have shown stronger association with T2DM and prediabetes. In clinical practice in Bangladesh, T-Chol, Tg, HDL-C, and LDL-C are the parameters available for monitoring lipid abnormalities.…”
Section: Discussionmentioning
confidence: 83%
“…Our study showed the prevalence of overweight and obese participants to be 29.3% (95% CI = 23.0–36.4%). A study conducted at other villages in Mustang district, Nepal, reported the prevalence of overweight and obese population at the rural setting to be 26.7% whereas at the urban settings to be 47.7% and 56.6% respectively [ 27 ]. A possible reason behind these differences may be associated with economic status.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is similar as in other findings examining the prevalence of IHG in different villages that have the same ethnic background as in our study. For instance, research at other villages in Mustang district has observed the prevalence of IHG ranging from 22.1–39.3% [ 27 ]. In addition, examining of the prevalence of IHG at the same altitude in China and India ranged from 22.3–41.6% [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 The result of our study is nearly comparable to the results of the study done in similar geographical region of Nepal by Aryal et al where Overall, 6.9% of participants residing in high altitude had diabetes or were on hypoglycaemic treatment. 3 Another study done by Woolcott et al in United States also revealed that diabetes was substantially less prevalent in high-altitude counties compared to low altitude counties (6.4% [5.4-7.3] and 9.1% [7.8-10.5]). 10 The study revealed male population had higher prevalence of diabetes mellitus in comparison with the female group ), P=0.003).…”
Section: Discussionmentioning
confidence: 95%
“…Hypoxia results in a preference for glucose utilization and decreases uptake of free fatty acids because of oxygen-deficient adaptation. 3 Also, the inhibition of gluconeogenesis in hepatocytes in intermittent hypoxia leading to smaller hepatic glucose output can be an important factor for decreased blood glucose profile in inhabitants of high altitude of Nepal. 4 Moreover, it can also be correlated with the reduced basal insulin level, 4 increased physical activity and dietary pattern in natives residing in mountains of Nepal.…”
Section: Introductionmentioning
confidence: 99%